Development of Student Guidebooks for Physical Education Learning Using The Flipped Classroom Model - Ferdiansyah, Arif; Kurniawan, Rama; Darmawan, Arief (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This study aims to develop and determine the validity level of the student guidebook for Physical Education learning with the flipped classroom model of volleyball overhead pass material class XI MAN 1 Malang. The type of research used is research and development by adapting the ADDIE development model by Branch, which consists of 5 stages of development include Analysis, Design, Development, Implementation, and Evaluation. The data analysis technique used in this research is descriptive quantitative with data collection instruments using questionnaires. The research subjects were 48 students and 2 physical education teachers at MAN 1 Malang. The Student Handbook has been validated by media experts, learning experts, and material experts. The results of the large group trial showed a percentage value of 93%. This student guidebook product can be concluded to be valid and suitable for use in physical education learning at MAN 1 Malang. With this student guidebook, it is hoped that it can provide convenience for grade XI students at MAN 1 Malang in carrying out learning volleyball overhead passing using the flipped classroom model.